2013
DOI: 10.1016/j.socscimed.2012.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Infant Death Syndrome (SIDS) risk reduction and infant sleep location – Moving the discussion forward

Abstract: Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Social science medicine. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reected in this document. Changes may have been made to this work since it was submitted for publication. A denitive version was subsequently published in Social science medicine, 79, 2013, 10.1016/j.socscimed.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 94 publications
(92 reference statements)
1
71
0
1
Order By: Relevance
“…Most studies that measured infant sleep practices utilized self-report data; a few included observational data. Some authors have argued that strong messaging on safe sleep practices has created a stigma around use of unsafe sleep practices [41][42][43], and thus, as noted by several of the study authors, a limitation of self-report data is that caregivers may under-report their use of unsafe sleep practices. Some studies have also found that despite high rates of SIDS knowledge among caregivers, most did not adhere to safe sleep recommendations [44,45].…”
Section: Evaluation Design/study Methodsmentioning
confidence: 96%
“…Most studies that measured infant sleep practices utilized self-report data; a few included observational data. Some authors have argued that strong messaging on safe sleep practices has created a stigma around use of unsafe sleep practices [41][42][43], and thus, as noted by several of the study authors, a limitation of self-report data is that caregivers may under-report their use of unsafe sleep practices. Some studies have also found that despite high rates of SIDS knowledge among caregivers, most did not adhere to safe sleep recommendations [44,45].…”
Section: Evaluation Design/study Methodsmentioning
confidence: 96%
“…For instance, non-biological conditions such as infant sleep position affect the likelihood of sudden infant death syndrome (SIDS), a leading cause of postneonatal death [48]. In Canada, SIDS consistently ranked among the top five leading causes of infant death between 2004 and 2008 [49].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep and lactation are intimate, intertwined aspects of postpartum life that are influenced by notions of the nature of infancy, the role of the parent and wider cultural beliefs, in addition to individual preferences and constraints 5. Tully et al 1 found that new mothers and postpartum healthcare providers feel that that there is excessive pressure on women adhering to guidelines instead of focusing on the contexts that promote or inhibit the realisation of personal goals.…”
Section: Commentarymentioning
confidence: 99%